Imbalance of the Gut Microbiota May Be Associated with Missed Abortions: A Perspective Study from a General Hospital of Hunan Province - Bingsi Gao; Xingping Zhao; Xinyi Liu; Xuan Yang; Aiqian Zhang; Huan Huang; Yu-ligh Liou; Dabao Xu (Journal of Immunology Research)
Objective. To conduct a preliminary investigation that shows the possible correlation between the change of gut microbiota and missed abortions (MAs), which further provides a new potential insight for the prevention and therapy of MAs. Method. One hundred women, including 50 patients with MAs (case group) and 50 normal pregnant women (control group), were enrolled in the study. Fecal specimens were collected in the first trimester. Bacterial DNA was extracted, hybridized with primers of specific genes, and then detected by bacterial chip. The composition and the relative abundance of the gut microbiota were compared and analyzed. Furthermore, Kyoto Encyclopedia of Genes and Genomes enrichment analysis was used to explore the relative pathways. Results. (1) The α-diversity and β-diversity of the gut microbiota in patients with MAs were significantly lower than that those in normal pregnant women (P<0.05). At the phylum level, Firmicutes, Proteobacteria, Actinomycetes, and Bacteroidetes accounted for the main proportion of intestinal flora in the 2 groups. Only Actinobacteria was high in the case group. Significant differences were found between the two groups at the phylum level (P<0.05). Prevotella, Lactobacillus, and Paracoccus were significantly more abundant in the control group than in the case group at the genus level (P<0.05). (2) KEGG pathway enrichment analysis found significant differences in 27 signaling pathways and metabolic pathways between the two groups of differentially expressed genes (all adjusted P<0.05). (3) The positive rate of M. hominins (MH) detection in the control group was significantly higher in the MA group (χ2=7.853, P=0.004). Conclusion. The high abundance of Actinobacteria in the MA group was the first time found and reported in the study. The dysbiosis of the gut microbiota correlates with MAs. This study provided insights into the potential change of gut microbiota of MAs and the potential underlying mechanisms through certain impaired lipid metabolism and aroused inflammation pathways. Comprehensive insights regarding gut microbiota may facilitate improved understanding and the development of novel therapeutic and preventive strategies for MAs.